Origin of the interest, motivation and environmental concern in socio-environmentally engaged young in the Manaus-AM metropolitan region - Paz, Damaris Teixeira; Higuchi, Maria Inês Gasparetto (Sustainability in Debate, 2018)
This research discusses aspects associated to the emergence of environmental interest in young people engaged in social and environmental collectives as well as the main motivations and concerns that led them to militancy of this nature. The qualitative research was carried out with 19 young people from six socio-environmental groups from three cities in the metropolitan region of Manaus-AM. The data obtained from semi-structured interviews indicated that the concerns about environmental problems of these young people are located mainly in broad areas. The contributions of family,teachers or friends and the coexistence with people already engaged in pro-environmental actions related to these problems, are pointed out as stimulators of interest and entry into social and environmental collectives. The initial interest in joining a group opens new avenues for learning and at the same time fulfills the youth's desire for greater social insertion.